Development of the reflective practice questionnaire: preliminary findings. Issue 1 (2nd January 2018) - Priddis, Lynn; Rogers, Shane L.
Abstract: This study introduces a new reflective practice questionnaire (RPQ) that can be used to assess self-reported measures for investigating the experiences, benefits, and potential pitfalls of reflective practice and reflective supervision. This questionnaire sets itself apart from previous self-report measures of reflective practice by the ability to administer to individuals working in any service industry (e.g. psychology, nursing, education, and others). This will allow for future investigations that can compare and contrast across different contexts and professions. This will further the understanding of how reflective practice impacts those engaged with the process. The present study provides preliminary evaluation of the questionnaire with samples from the general public (Study 1), and mental health practitioners (Study 2). The questionnaire includes a number of short four-item sub-scales for evaluating reflective practice including: reflective-inaction; reflective-on-action; reflective with others self-appraisal; desire for improvement; confidence (general); confidence (communication); uncertainty; stress interacting with clients; and job satisfaction. A six-item attitude towards reflective supervision scale is also included in the research. Results suggest that reflective practice can foster confidence and further a desire for self-improvement. However, results also indicate how reflective practice might increase uncertainty and stress in some individuals. Study 2 reveals that a more positive appraisal of reflective supervision is associated with greater selfreported reflection, desire for improvement, and confidence.